Outing Class as a Strategy to Strengthen Merdeka Curriculum Implementation: Kegiatan Lapangan sebagai Strategi untuk Menguatkan Pelaksanaan Kurikulum Merdeka - Nailirrohmah; Arifin, Moch. Bahak Udin By (Indonesian Journal of Education Methods Development, 2025)
Background: The Merdeka Curriculum emphasizes flexible and contextual learning, yet limited interactive learning resources in several schools hinder its optimal implementation. Specific Background: SDN Candiharjo has applied Outing Class activities, but no empirical evidence has been documented regarding their contribution to curriculum effectiveness. Gap: Previous studies highlighted benefits of outdoor learning, but none assessed its direct role in strengthening the Merdeka Curriculum within this specific school context. Aim: This study examines the effectiveness of Outing Class in supporting the Merdeka Curriculum and evaluates its contribution to students’ learning outcomes. Results: Using a sequential explanatory mixed-method design, the study shows a significant improvement in students’ scores, with the average increasing from 59.16 to 78.57, and the minimum score rising from 36 to 76. Observations and interviews confirm enhanced engagement, contextual understanding, and social interaction. Novelty: This study provides the first empirical evidence of Outing Class implementation in SDN Candiharjo within the IPAS subject, focusing on the integration of local cultural sites as learning resources. Implication: Findings support the integration of contextual outdoor learning as a practical strategy for strengthening the application of the Merdeka Curriculum in elementary schools. Highlights:• Significant learning improvement after Outing Class• Integration of local culture for contextual learning• Strengthened implementation of Merdeka Curriculum Keywords: Merdeka Curriculum, Outing Class, Contextual Learning, Elementary School, Learning Outcomes